The application of project-based learning in graduate courses: a case study in China - Han, Fusong; Xu, Jun; Peng, Yi; Yu, Chengqun (Frontiers in Education, 2026)
With the rapid expansion of graduate enrollment in China, curriculum teaching reform has become crucial for enhancing the quality of innovative talent cultivation. This study investigates the effectiveness of Project-Based Learning (PBL) in graduate education reform and identifies key implementation challenges. An experimental study was conducted in the “Rural Social Survey and Research Methods” course at Hunan University of Technology, involving 60 master’s students specializing in rural development. Participants were randomly assigned to either a control group or an experimental group, with both groups taught by the same instructor. After the course concludes, a Likert scale is used to evaluate students’ recognition of the course. Additionally, 50 full-time teachers from Hunan University of Technology were randomly surveyed regarding their views on PBL. The results demonstrate that compared to traditional methods, the application of PBL significantly improved students’ self-directed learning abilities and research competencies. The primary determinants influencing teachers’ adoption of PBL were identified as: habitual pedagogical dependencies, insufficient instructional resources, and lack of project implementation experience. 76.19, 76.19, and 71.43% of the surveyed teachers believed that habitual pedagogical dependencies, insufficient instructional resources, and lack of project experience, respectively, led to their reluctance to adopt project-based teaching methods. 42.86% of the surveyed teachers indicated that excessively large class sizes also contributed to their reluctance to adopt project-based teaching methods.